What a fool believes : a memoir - McDonald, Michael, 1952-; Reiser, Paul (Dey Street Books, 2025)
"A sweeping and evocative memoir from the Rock Roll Hall of Famer, Grammy Award-winning, platinum selling singer-songwriter Michael McDonald, written with his friend, Emmy Award-nominated actor, comedian, and #1 New York Times bestselling author Paul Reiser. Doobie Brothers. Steely Dan. Chart topping soloist. Across a half-century of American music, Michael McDonald's unmistakably smooth baritone voice defined an era of rock and RB with hit records like "What A Fool Believes," "Takin' It to the Streets," "I Keep Forgettin'," "Peg," "It Keeps You Running," "You Belong to Me," and "Yah Mo B There." In his candid, freewheeling memoir, written with his friend, the Emmy Award-nominated actor and comedian Paul Reiser, Michael tells the story of his life and music. A high school dropout from Ferguson, Missouri, Michael chased his dreams in 1970's California, a heady moment of rock opportunity and excess. As a rising session musician and backing vocalist, a series of encounters would send him on a wild ride around the world and to the heights of rock stardom--from joining Steely Dan and becoming a defining member of The Doobie Brothers to forging a path as a breakout solo RB artist. Interwoven with the unforgettable tales of the music, Michael tells a deeply affecting story of losing and finding himself as a man. He reckons with the unshakeable insecurities that drove him, the drug and alcohol addictions that plagued him, and the highs and lows of popularity. Along the way he relays the lessons he's learned, and that if he's learned anything at all it's that there's often little correlation between what you get and what you deserve. Filled with unbelievable stories and a matchless cast of music greats including James Taylor, Ray Charles, Carly Simon, and Quincy Jones, What a Fool Believes is a moving and entertaining memoir that is sure to be a classic"--